Pengaruh Electronic Word of Mouth, Pengalaman Pelanggan, dan Kepercayaan terhadap Minat Beli pada FamilyMart Pahlawan Revolusi - Wahid Pasha Purnama; Adnan Kasofi; Sabo Hermawan (Indonesia Economic Journal, 2026)
The phenomenon of competition in the modern retail industry in Indonesia is increasing along with changes in consumer behavior and the rapid growth of digital information. Although FamilyMart has successfully expanded its outlets across various regions, a decline in the Top Brand Index indicates problems in non-physical aspects such as customer perception, shopping experience, and trust. This study aims to analyze the influence of Electronic Word of Mouth, Customer Experience, and Trust on Purchase Intention at FamilyMart Pahlawan Revolusi. The research employed a quantitative approach using a survey method through questionnaires distributed to FamilyMart Pahlawan Revolusi customers and was analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results show that Electronic Word of Mouth has a positive and significant effect on Purchase Intention. Customer Experience also has a positive and significant effect on Purchase Intention, where comfortable shopping experiences, adequate facilities, and transaction convenience can increase customers’ buying interest. In addition, Trust has a positive and significant influence on Purchase Intention, indicating that customers’ confidence in product quality, service, and company consistency plays an important role in shaping purchase intention. These findings confirm that the combination of digital reviews, direct customer experience, and trust level are key determinants in increasing customer Purchase Intention in modern retail, particularly FamilyMart. Therefore, companies need to improve service quality, maintain positive online reviews, and continuously build customer trust as part of future marketing strategies.